Light - reaching for the moon : Ingo Maurer. - Von Vegesack, Alexander, 1945-; Eisenbrand, Jochen, 1970- (Weil am Rhein : Vitra Design, 2004)
An itinerary along the work of this designer of light called by many as "the poet of light" or "the wizard of light".
Keywords: Verlichting; Verlichtingsarmaturen